Model Penanganan Pelanggaran Kode Etik Penyelenggara Pemilu di Kabupaten Karawang - Siti Hamimah; Rengga Kusuma Putra (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
The election organizers are regulated in Law Number 7 of 2017 as institutions that organize elections, consisting of the General Election Commission (KPU), the Election Supervisory Agency (Bawaslu), and the Honorary Council of Election Organizers (DKPP) as a unified election task force. The supervisory board elects members of the council, parliament members, representatives of state bodies, the president and vice president, as well as members of the people's representative council directly from the people. To implement Law No. 7 of 2017, the independence and autonomy of election organizers are required. These institutions will later have specific regulations to handle violations committed by election organizers. The mechanism for resolving violations by election organizers is regulated in DKPP Regulation Number 2 of 2019. This regulation contains several procedural rules for DKPP sessions, which then result in final and binding decisions. The problem formulation in this writing includes, How is the concept of handling ethical code violations of election organizers, and How to find an ideal model for handling ethical code violations of election organizers. The research method used is normative juridical writing. The handling of electoral criminal offenses, which has not been optimal as described above, is due to the supervisory scope of Bawaslu, as mandated by the Election Law, not being implemented maximally. Article 486 paragraph (2) stipulates that "Gakkumdu as referred to in paragraph (1) is attached to Bawaslu, Provincial Bawaslu, and Regency/Municipal Bawaslu" and Article 486 paragraph (4) states that "Investigators and prosecutors as referred to in paragraph (3) carry out their duties full-time in handling election criminal offenses." These two provisions emphasize that the scope of control over the process of handling electoral criminal offenses conducted by the Gakkumdu center lies within Bawaslu, not within each institution.